2011
DOI: 10.1038/cr.2011.34
|View full text |Cite|
|
Sign up to set email alerts
|

HDAC2 phosphorylation-dependent Klf5 deacetylation and RARα acetylation induced by RAR agonist switch the transcription regulatory programs of p21 in VSMCs

Abstract: Abnormal proliferation of vascular smooth muscle cells (VSMCs) occurs in hypertension, atherosclerosis and restenosis after angioplasty, leading to pathophysiological vascular remodeling. As an important growth arrest gene, p21 plays critical roles in vascular remodeling. Regulation of p21 expression by retinoic acid receptor (RAR) and its ligand has important implications for control of pathological vascular remodeling. Nevertheless, the mechanism of RAR-mediated p21 expression in VSMCs remains poorly underst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
58
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 77 publications
(60 citation statements)
references
References 68 publications
2
58
0
Order By: Relevance
“…RAR␣ has been shown to distinctly mediate the growth inhibitory effect of retinoids and therefore is a potential target of research for preventive treatment of vascular proliferation disease (24). In VSMCs, we discovered that treatment with ATRA induced the expressions of KLF4 and RAR␣.…”
Section: Discussionmentioning
confidence: 74%
See 2 more Smart Citations
“…RAR␣ has been shown to distinctly mediate the growth inhibitory effect of retinoids and therefore is a potential target of research for preventive treatment of vascular proliferation disease (24). In VSMCs, we discovered that treatment with ATRA induced the expressions of KLF4 and RAR␣.…”
Section: Discussionmentioning
confidence: 74%
“…Although retinoid signaling is considered responsible for the direct binding of RARs/RXRs to RAREs in target gene promoters, other evidence has shown that RARs exert their effect by interacting with other general transcription factors, such as Sp1, Ets-1, cAMP response element-binding protein, and KLF5 (24,26,36,39). There are three GC boxes in the proximal region of the Klf4 promoter, which may play a vital role in Klf4 transactivation (9,18).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Co-immunoprecipitation was performed as described previously [24]. In brief, proteins from VSMCs were first pre-cleared with 30 μl of protein A-agarose (50% v/v).…”
Section: Co-immunoprecipitation Assaymentioning
confidence: 99%
“…Specifically, KLF5, retinoic acid receptor (RAR)-α, and HDAC2 interact at the p21 promoter to repress its expression and induce proliferation in VSMCs (40). When stimulated with a RAR-α agonist, HDAC2 deacetylates KLF5 to dissociate it from the p21 promoter.…”
Section: Histone Acetylation In Cardiovascular Diseasementioning
confidence: 99%